THE ROLE OF INNOVATION IN THE SUCCESSION OF FAMILY BUSINESSES - Tóth, Boglárka (APSTRACT: Applied Studies in Agribusiness and Commerce, 2024)
Generational change and innovation are at the heart of the future success of a family business. Therefore, it is clear that the generational change of family firms should be considered from an innovation perspective. Despite this, there is no research in the literature that examines the importance of innovation in succession. In this article, the role of innovation in the succession process is examined by surveying 76 Hungarian family business owners and their potential successors. The aim of the article is to explore whether innovation plays a role in the life of the business and, if so, whether it can make succession more successful. In addition, whether the willingness of the successor to innovate is more important than the choice of successor within the family, and whether potential successors have innovative ambitions. Results include that family business owners who consider innovation important can be considered as partially conscious generational succession planners, as they are more likely to already have a potential successor than owners who do not consider innovation important. Overall, the family business owners surveyed do not consider it more important that the successor be a family member or that the successor have an innovative approach, but first and second generation owners have different views. Second-generation family business owners now place much less importance on having a successor from the family than founders, and all second-generation completers placed the highest value on the successor's willingness to innovate, while founders placed significantly lower value on this. Nevertheless, none of the owners surveyed had a potential successor outside the family. Finally, innovation plays an important role in the future goals of successors. They consider continuous improvement and innovation to be the most important goal after stable and profitable operation of the company and the realisation of their own career, and prefer to implement business process innovations rather than product innovations.